2020
DOI: 10.1002/cite.202000176
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fluid Dynamic Stress in Stirred Bioreactors – The Scale of the Biological Entity: A Personal View

Abstract: From the start of industrial biotechnology, there has been a perception that biological entities are damaged by stirring, so‐called ‘shear damage'. Often, it was the soft option to explain a loss of performance when it was due to other factors, such as bubble ingestion with proteins or on scale‐up, where tip speed increased when it was due to decreased homogeneity, especially in pH. For many years, poor control and the range of analytical tools available made a more in‐depth explanation difficult; and the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 64 publications
1
24
0
Order By: Relevance
“…We have discussed this in detail previously (Nienow et al 2014 ) and though rapid increases in the impact stresses with increasing speed have proved to be an effective way of detaching cells from microcarriers in the presence of detachment enzymes during harvest, there is no evidence to suggest that damage occurs either during that process or culture at N JS . On the other hand, it has also been found that the impact of fluid dynamic stress from turbulence can be effectively considered in relation to the size of the Kolmogorov scale in relation to the size of the biological entity (Nienow 2020 ). Typically, in brief, if the size of the biological entity is less than the Kolmogorov scale, λ K , the cell will not be damaged in stirred bioreactors.…”
Section: Resultsmentioning
confidence: 99%
“…We have discussed this in detail previously (Nienow et al 2014 ) and though rapid increases in the impact stresses with increasing speed have proved to be an effective way of detaching cells from microcarriers in the presence of detachment enzymes during harvest, there is no evidence to suggest that damage occurs either during that process or culture at N JS . On the other hand, it has also been found that the impact of fluid dynamic stress from turbulence can be effectively considered in relation to the size of the Kolmogorov scale in relation to the size of the biological entity (Nienow 2020 ). Typically, in brief, if the size of the biological entity is less than the Kolmogorov scale, λ K , the cell will not be damaged in stirred bioreactors.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of agitation speed while scaling up fermenters is mainly practised to maintain sufficient shear stress between the impeller blades and vessel wall (Junker 2004 ). As a result, uniform mixing is achieved with minimum microbial cell damage (Nienow 2021 ). The industrial scale fermenter was found to have a lower specific energy or P/V w value than lab and pilot scale fermenters (Table 3 ) and observed to be lower than the range of values (2–10 kWm −3 ) suggested by Meyer et al ( 2017 ) for pilot scale fermentations.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, the greater torque was associated with greater energy consumption, which increased with an increase in agitation speed, but it is interesting to note that RTB was calculated to have 1.9 times greater torque output than LA315 at similar specific energy consumption (~2.8 or 4.31 kW m −3 at Z = 6 or 9.29 m) and lower agitation rate (1.33 s −1 ). Moreover, Nienow ( 2021 ) indicated that microbial cells may remain unaffected by the hydrodynamic stress if the cell size is smaller than Kolmogoroff microscale of turbulence ( λ k ), which was calculated using Eq. 6 and 7 .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, velocity fluctuations (turbulent intensity) help to improve the mixing process [19]. Some authors have found that there is a close interaction between the morphology, the broth rheology, and the turbulent intensity in submerged fungal fermentations in stirred tank reactors [20][21][22]. On the other hand, the turbulent intensity can be linked to the strain rate.…”
Section: Introductionmentioning
confidence: 99%